PENGARUH GAYA KEPEMIMPINAN, STRES KERJA DAN KOMPENSASI TERHADAP SEMANGAT KERJA DAN KINERJA KARYAWAN PT. BANK RAKYAT INDONESIA KANTOR CABANG SUDIRMAN PEKANBARU - Syafriani, Nony; maulida, Yusni (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to determine the influence of leadership style, work stressand compensation on morale and performance of employees of Bank Rakyat IndonesiaBranch Office Sudirman Pekanbaru. The analytical method used in this research is descriptivestatistical analysis and inferential statistics through Multiple RegressionAnalysis.This research method used survey method, with a total population of 132 respondentswere entirely permanent employees of Bank Rakyat Indonesia Branch OfficeSudirman Pekanbaru. Before testing the hypothesis, test the validity and reliability of theprimary data questionnaire using SPSS version 17.0. The regression equation was thentested with an analysis of the classical assumption of normality test, multiolinieritas,heterocedasticity test, and autocorrelation test. Analysis of the influence depeden andindependent variables was analyzed with t-test, F, determinant coefficient (R Â²) and correlationcoefficient (R)Results of research addressing partially and simultaneously factorleadership style, job stress and compensation has a positive and significant impact onmorale and performance of employees of Bank Rakyat Indonesia Branch Office SudirmanPekanbaru.